Comment on "Quantum effects in spontaneous emission by a relativistic, undulating electron beam" by Robb G.R.M. and Banifacio R. - Potylitsyn A. P. Alexander Petrovich (2012, 2012)
В фонде НТБ ТПУ отсутствует